Temperature control system on greenhouse effect gaplek dryer - Bandiyah Sri Aprillia; Brahmantya Aji Pramudita; Prisma Megantoro (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Gaplek is a processed product of cassava that requires a drying process to remove the water content in cassava. Solar thermal energy can be used for the drying process of gaplek by using a greenhouse effect drying system. However, the greenhouse effect drying system using solar thermal energy is very dependent on weather conditions and temperature that is difficult to control. Therefore, a temperature control system is proposed in this study by utilizing Pulse Width Modulation (PWM) to control the exhaust fan speed. Thus, the temperature can be maintained according to the drying standard of processed cassava products. In this study, a temperature control system has been successfully created that is able to maintain the temperature in the drying room according to the drying standard, namely at a temperature of 50℃ to 60℃ when tested in three different locations, namely, Sukamaju Village, Kaligunting Village, and Sumberejo Village which have shown optimal drying temperature.